Structure and phase behavior of the expanded-metal compound 7Li(ND3)4. - Ibberson, R; Fowkes, A; Rosseinsky, M; David, W; Edwards, P (2009)
Metal lite: High-resolution neutron powder diffraction data reveals that the body-centered cubic crystal structure of lithium(0)tetraamine transforms to a simple cubic structure below 22 K. The detailed structure determinations will allow new insights into the coupled structural and electronic properties of the lightest metal.